2023
DOI: 10.1097/dcr.0000000000002615
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Functional Outcomes After Intersphincteric Resection for Ultralow Rectal Cancer: A Prospective Observational Study

Abstract: BACKGROUND: Intersphincteric resection is the ultimate sphincter-preserving surgical technique for ultralow rectal cancer, but quality-of-life changes after surgery remain unclear. It is also unknown which questionnaire has better associations with functional results for capturing clinical variation in quality of life.OBJECTIVE: This study aimed to assess change in the quality of life and its correlation with functional outcomes among patients undergoing intersphincteric resection for ultralow rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…[2][3][4] However, in terms of functional concerns, low anterior resection syndrome (LARS) development is virtually inevitable after ISR because of a multiple surgery-and patient-related factors. [5][6][7][8][9] The LARS score and the Wexner incontinence score (WIS) are frequently adopted as patient-reported outcome measures to evaluate bowel dysfunction after rectal surgery. Although both are quick evaluation tools, the former underestimates the impact of evacuatory dysfunction, and the latter focuses only on fecal incontinence.…”
Section: Medidas Principales De Resultadomentioning
confidence: 99%
See 3 more Smart Citations
“…[2][3][4] However, in terms of functional concerns, low anterior resection syndrome (LARS) development is virtually inevitable after ISR because of a multiple surgery-and patient-related factors. [5][6][7][8][9] The LARS score and the Wexner incontinence score (WIS) are frequently adopted as patient-reported outcome measures to evaluate bowel dysfunction after rectal surgery. Although both are quick evaluation tools, the former underestimates the impact of evacuatory dysfunction, and the latter focuses only on fecal incontinence.…”
Section: Medidas Principales De Resultadomentioning
confidence: 99%
“…[10][11][12] Previous studies have demonstrated a functional recovery after ISR, but a high prevalence of LARS may persist for years. 9,13,14 It is important to note that the functional scores could not accurately mirror the real-world impact of LARS on quality of life (QoL). In clinical practice, colorectal surgeons are always confused about how some patients with major LARS can live active lives, whereas others with minor LARS have even worse QoL.…”
Section: Medidas Principales De Resultadomentioning
confidence: 99%
See 2 more Smart Citations
“…Xu et al 19 found no difference in the incidence of postoperative complications in patients undergoing total neoadjuvant therapy as opposed to neoadjuvant chemoradiation for rectal cancer. Zhang et al 20 reported on the quality of life and functional outcomes following intersphincteric resection for “ultra-low” rectal cancer. They observed that low anterior resection syndrome persists for years but that functional and condition-specific outcomes improve over time.…”
Section: Technical Aspects Of Surgery Effects Of Treatment On Surgery...mentioning
confidence: 99%